2021
DOI: 10.1016/j.agsy.2021.103088
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the contribution of 16 European beef production systems to food security

Abstract: CONTEXTLivestock production, and more particularly ruminants, is criticized for its low conversion efficiency of natural resources into edible food. OBJECTIVEThe objectives of this paper are to propose an evaluation of the contribution to food security of different European cattle farms through three criteria: 1) food production assessed by the amount of human-edible protein (HEP) and energy (HEE) produced at farm level, 2) feed-food competition at the beef production scale estimated in terms of net human-edib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 21 publications
0
16
0
Order By: Relevance
“…(2019) and Mosnier et al . (2021). They also demonstrated that cattle fed with inedible fodder are efficient producers of ASF (Wilkinson, 2011; van Zanten et al ., 2016; Laisse et al ., 2018; Mosnier et al ., 2021).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…(2019) and Mosnier et al . (2021). They also demonstrated that cattle fed with inedible fodder are efficient producers of ASF (Wilkinson, 2011; van Zanten et al ., 2016; Laisse et al ., 2018; Mosnier et al ., 2021).…”
Section: Discussionmentioning
confidence: 99%
“…(2019) and Mosnier et al . (2021), for example, compared pasture-based cattle systems with concentrate-based cattle systems and concluded that unlike pasture-based cattle, concentrate-based cattle are inefficient protein producers. Their results on monogastric pigs also correspond to ours whereby, pig systems fed with HDP intense grains are demonstrated to be inefficient HDP producers (Wilkinson, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations